Elaborately designed polymer dielectric films with low coefficient of thermal expansion demonstrating high and stable electrostatic energy density over a wide temperature range. (December 2022) - Yu, Junyi; Wang, Lin; Liang, Zeyu; Xu, Pengpeng; Min, Yufeng; Liu, Zheng; Huang, Juchen; Luo, Suibin; Yu, Shuhui; Sun, Rong
Abstract: High-temperature electrostatic energy storage dielectric capacitors with the prominent advantage of ultrahigh power density have recently become a focal point in the field of power electric and electronic systems to adapt the harsh working environment. To reduce the decreasing degree of electric breakdown strength with the increase in temperature is the key to maintaining a high energy density at elevated temperature. Herein, we analyzed thermal and electric properties of a series of films and interpreted the relationship between the capability of dimensional deformation and electric breakdown strength in view of molecular dynamics. Based on the results, an empirical law, ln(Eb ) = kln(1/α-n)+C, was proposed, which relates electrical and thermal performance of low thermal conductivity dielectric materials for achieving stabilized high-temperature energy storage density. Guided by this finding, the meticulously prepared silicon oxide/epoxy films with low thermal expansion coefficients present a high charge–discharge efficiency of 86% at 200 °C, resulting in a discharged energy density of 2.1 J/cm 3 . Designing polymer dielectrics with low thermal expansion coefficients in a wide temperature range proves effective to obtain excellent energy storage performance at ultrahigh temperatures. Graphical abstract: Image 1 Highlights: An empirical law ln(Eb )=kln(1/α-n)+C was proposed which relates electrical and thermal property of polymer-based materials. Eb is electric breakdown strength, α is coefficient of thermal expansion and k, n, and C constants for a specific polymer. It indicates a high Eb and discharge energy storage density (Ud ) can be achieved by designing a material with low α. SiO2 /epoxy composite films were elaborately fabricated with a low α (5–200 °C) of 56.1 ppm/K. The film has a charge-discharge efficiency upto 86% and Ud of 2.1J/cm 3 at 200 °C, celebrating a high temperature stability.